MBL2 Genotypes and Their Associations with MBL Levels and NICU Morbidity in a Cohort of Greek Neonates - Matthaios Speletas; Antonios Gounaris; Eirini Sevdali; Maria Kompoti; Katerina Konstantinidi; Rozeta Sokou; Elena Tsitsami; Anastasios E. Germenis (Journal of Immunology Research)
The objective of this study was to assess the frequency of MBL2 genotypes and their associations with MBL levels and various morbidities of a neonatal intensive care unit (NICU). One hundred and thirty-four (134) NICU (83 term and 51 preterm) and 150 healthy neonates were enrolled in the study. MBL2 genotype and MBL serum levels at birth were determined prospectively by PCR-RFLP-sequencing and enzyme-linked immunosorbent assay, respectively. NICU neonates displayed significantly lower MBL serum levels compared to healthy ones. MBL deficiency, defined as the low MBL2 expression group (XA/O and O/O), was significantly associated with an increased risk of respiratory morbidity, especially transient tachypnea of the newborn and respiratory distress syndrome (RDS). Moreover, an increase of 100 ng/mL of serum MBL levels decreases by 5% the risk of total respiratory morbidity and by 7% the risk of RDS, after correction for prematurity and sex and regardless of the presence of infections. Our study further supports the notion that neonates with MBL deficiency and low MBL serum levels at birth may be at higher risk of developing severe respiratory complications.